Cloud-Enabled Innovation in Retail: Transforming Inventory Management and Demand Forecasting - Chaitanya Teja Musuluri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the transformative impact of cloud computing technologies on the retail industry, examining core platform solutions, implementation strategies, and future trends. The article investigates how cloud integration has revolutionized inventory management, demand forecasting, and operational efficiency across the retail sector. Through detailed case studies of major retailers, the research demonstrates the substantial benefits of cloud adoption in areas such as real-time data processing, predictive analytics, and supply chain optimization. The article encompasses technical considerations, best practices, and emerging technologies, providing insights into successful implementation strategies and operational guidelines. The article further evaluates the integration opportunities and standardization initiatives shaping the future of retail cloud computing, highlighting the critical role of artificial intelligence, blockchain, IoT, and advanced analytics in driving industry innovation.
Keywords: Cloud Computing in Retail; Inventory Management Optimization; Predictive Analytics Implementation; Digital Transformation ROI; Retail Technology Integration